Measurements & dimensioning for a system for reconstructing 3-D objects from photographs - Ang, Jia Sheng (2019)
A research was set out to study the ability to reconstruct a 3-D model using a single 2-D photograph through photogrammetry. The result of this research is a program that successfully does so but lacks the capabilities to do viewing transformation as well as engineering dimensioning. The scope of this final year project is to address this issue and work towards implementing such capabilities into the software currently being developed. It is important to note that these capabilities are not novel but necessary for the software. Viewing transformation allows users to alter the orientation and position of the view point and the scale of the display, enabling them to make better use of the information. Engineering dimensioning essentially provides measurements on the object and has many applications. The method taken to implement the capabilities used the OpenGL graphics library on a C++ programming platform. Albeit successful, the method has its limitations and requires a smarter framework to realise the full potential. Hence, future development of the software and areas of improvement are also highlighted and discussed.